Олика в історії музейної справи - Рябчикова, Фаїна; Riabchykova, Faina (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті на прикладі Олики розглянуто окремі аспекти розвитку вітчизняної музейної справи. Охарактери-зовано домузейне колекціонування в цьому населеному пункті, націоналізацію та розпорошення збірок Радзивіллів, виникнення й занепад громадського музею, а також висловлено окремі зауваги щодо подальшої музеєфікації культурної та природної спадщини містечка. The paper gives an analysis of collecting practices in Olyka, further nationalization and division of collections, the emergence and decline of public museum. Also, it is presented some comments on the musealisation of cultural and natural heritage of the town. The author believes that for actualization of cultural heritage it is more promising to musealize not just separate objects, but all historical, cultural and natural environments including whole their movable, immovable, intangible objects and with participation of local residents. Such approach could be fulfilled in the way of creation «environmental» museum or ecomuseum. It should cover the entire historical territory of the town including the castle, historical and religious buildings, necropolises, objects of nature.
Olyka in the History of Museums
Keywords: Олика; Радзивілли; музейна справа; музеєфікація; Olyka; Radzivills; museum studies; musealisation